The Biophysical Controls of Macroalgal Growth on Subtropical Reefs - Cordeiro, Cesar Augusto Marcelino Mendes; Harborne, Alastair R.; Ferreira, Carlos Eduardo Leite (Frontiers in Marine Science, 2020)
The importance of macro-grazers in controlling macroalgal cover has long been recognized on tropical and temperate reefs, with fishes of primary importance on the former and sea urchins on the latter. However, the functional role of herbivorous urchins and fishes on subtropical marginal reefs remains poorly explored. To evaluate the relative importance of fishes and urchins on marginal subtropical reefs, this study used exclusion devices (excluding all grazers, fishes, or urchins) at two depths (1-2, 5-6 m) on Brazilian rocky reefs. Depth influenced responses within cages, with shallow sites changing from patchy barrens (dominated by crustose coralline algae) to epilithic algae-dominated within exclusion treatments, and sea urchins being the primary driver of benthic dynamics. In deeper water, the growth and senescence cycle of Sargassum species was associated with upwelling events during the spring and summer, and dominated benthic dynamics. No clear influence of herbivorous fishes was detected on benthic cover at either depth, despite biomasses similar to comparable tropical reefs where they do control macroalgal populations. Thus, abiotic factors seem to be a strong driver of benthic dynamics in the studied region, and top-down processes act only at shallow depths. Consequently, despite Brazilian subtropical communities being dominated by tropical species, the ecological drivers of these reefs may be more similar to temperate systems.